USE OF INNOVATIVE TECHNOLOGIES IN RUSSIAN LANGUAGE CLASSES - THE WAY TO IMPROVE THE EDUCATIONAL PROCESS - Адылова Дилором Кадыровна (Journals Park Publishing, 2024)
In the modern world, the changed requirements and the need to study the Russian language have determined new methods and goals of teaching in the structure of continuing education. In language teaching, trends are taking shape that correspond to the current level of technological progress. The effectiveness of the use of information technologies in Russian and foreign language classes is no longer in doubt. Scientists note that the more perceptual systems involved in learning, the better and more firmly the material is assimilated. The active introduction of innovative technologies in the educational process multiplies didactic opportunities, providing visuals, audio and video support and control, which generally contributes to improving the level of teaching.
Keywords: modernization, innovative technologies, computer programs, electronic educational and methodological complex, educational process.